Temporal regularity in audition - Rajendran, V (2017)
Sound, by its very nature, is a temporal phenomenon. Everything from the perception of pitch to the sense of closure at the end of a symphony, relies on the brain's ability to integrate information over time. Ultimately it is perception that enables the richness of our interactions with the world around us, and it is a remarkable feat that the brain can quickly and accurately sift through the flood of information entering the ears to construct a coherent yet dynamic internal representation of the external world. Underlying this feat in part is the brain's ability to rapidly detect temporal patterns over timescales that span orders of magnitude, from sub-milliseconds to tens of seconds. Of particular interest is the ability to detect rhythms, or sound patterns in the range of hundreds of milliseconds to seconds. This timescale is particularly fascinating because it is critical to the perception of rhythm and beat in music, an ability that comes surprisingly naturally to us despite its neural underpinnings being far from understood. It is not just musical beat perception that remains mysterious; even the brain's mechanisms for detecting simple temporal patterns at this timescale are still not known. The work in this thesis therefore explores two broad questions that are key to understanding temporal processing at the rhythm timescale: 1- what are the perceptual consequences of rhythmic temporal regularity in sound? and 2- how does the brain detect temporal regularities at the rhythm timescale? I combine human psychoacoustics, rodent electrophysiology, and computational modelling to demonstrate that rhythmic sound patterns are easier to detect than arrhythmic ones, that adaptation in the auditory system may be a mechanism by which information about temporal structure at the rhythm timescale is encoded and made available to higher structures, and that low-level auditory processing may play a substantial part in shaping complex percepts such as where and how clearly we feel the beat in music.